Pengaruh Penggunaan Gawai terhadap Pemenuhan Hak Tumbuh Kembang dan Bermain Anak - Ramadhani, Riska (Jurnal Litigasi Amsir, 2022)
The use of gadgets in children can affect children’s growth and development and play. In the child’s growth and development, it will have an impact on the cognitive, physical, motor, emotional, social and language aspects of the child, while playing which is an important factor in the formation of a child’s identity can be disrupted by the presence of gadgets. The sophistication of the features of the device distracts children, by providing favorite viewing options on the Youtube application, playing online games, using social media and learning tools. Excessive use of gadgets in children in fact has an influence on the fulfillment of children’s rights, especially the right to a healthy body that will make optimal development and children’s right to play. Lack of awareness of the role and responsibility of parents in providing the use of gadgets in children hampers the growth and development of children.